Using plasma polymerised allylamine to culture hepatocytes in in-vitro fluidic bioreactor - Dehili, Chafika (2008)
Tissues constituting mammalian organisms are finitely organised 3-D multicellular structures where cell-cell and cell-matrix interactions are important modulators of functionality. The liver, being the site of metabolism in mammals, is extensively employed in in-vitro studies such as toxicology, drug testing and liver replacement. Most existing liver models have been static, homogenous 2-D models which have shown limited morphological and functional characteristics of in-vivo liver. With the improved understanding of the liver, these models became more sophisticated to comprise various liver and non-liver cell types, various configurations of extracellular matrix and complex scaffold supports, including fluidic systems. Fluidic supports for liver cells in-vitro are reported in this work and two different types were investigated. The first one was a glass based micro fluidic system with hexagonal structure to mimic the liver lobule. The second one was a standard flatplate fluidic chamber made of plastic (Ibidi channel). For the purpose of improving the attachment of the cells and the performance of the bioreactors examined, various substrate coating procedures were evaluated. The main coating techniques employed were collagen in two forms, adsorbed and gel, and plasma polymerised allylamine (ppAAm). The plasma coating procedures utilised in this work changed the surface properties of the substrate used by increasing the levels of nitrogen and improving hydrophilicity as demonstrated by x-ray photoelectron spectroscopy and contact angle measurements. The ppAAm penetrated both etched glass channels of the hexagonal bioreactor and the flat-plate chamber. The ppAAm films on etched glass channels had similar properties to the films produced on the glass surrounding the channels and coverslips. The ppAAm films obtained in the flat-plate chamber were different and they were characterised with a gradient of chemicals and hydrophilicity. This was because the Ibidi chamber is a closed environment and the plasma vapour infiltrated through the inlet and outlet at the ends of the channel. The attachment and functionality of primary rat hepatocytes seeded onto ppAAm films were evaluated using ppAAm coated coverslips and compared to coverslips coated with collagen gel. This demonstrated that both collagen gel and ppAAm improved the attachment, albumin secretion and 7-Ethoxyresorufin-O-deethylase (EROD) activity of the cells compared to uncoated glass. The hexagonal glass bioreactor showed poor attachment of liver cells and this was enhanced with ppAAm coating. The Huh-7 cells incubated into ppAAm coated hexagonal bioreactor died and detached after incubation with media flow. One of the reasons for this was poor cellular attachment. An improved attachment, but not viability, was observed when the cells were seeded using the biotin-avidin technique. The ppAAm coated flat-plate chamber demonstrated low adhesion of primary rat hepatocytes. However, these channels showed good attachment when collagen type I was adsorbed onto the surface. The viability and functionality, when measured using albumin secretion and EROD, of primary rat hepatocytes were maintained for 5 days in closed fluidic circuit in mono-culture and co-culture with 3T3 cells. These promising results could be exploited to further develop these systems for in-vitro culture of liver cells.